2017
DOI: 10.1098/rstb.2016.0281
|View full text |Cite
|
Sign up to set email alerts
|

SUMO, a small, but powerful, regulator of double-strand break repair

Abstract: The response to a DNA double-stranded break in mammalian cells is a process of sensing and signalling the lesion. It results in halting the cell cycle and local transcription and in the mediation of the DNA repair process itself. The response is launched through a series of post-translational modification signalling events coordinated by phosphorylation and ubiquitination. More recently modifications of proteins by Small Ubiquitin-like MOdifier (SUMO) isoforms have also been found to be key to coordination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 171 publications
5
65
0
Order By: Relevance
“…Emerging evidences revealed that small ubiquitin‐like modifiers (SUMOs) such as SUMO‐1, SUMO‐2, and SUMO‐3 in mammalian systems are found covalently attached to more than 50 proteins including p53, androgen receptor, IkBα, c‐jun, histone deacetylases (HDACs), and other proteins with major functions of SUMOylation, cytoplasmic nuclear transport, transcripton, and DNA repair …”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences revealed that small ubiquitin‐like modifiers (SUMOs) such as SUMO‐1, SUMO‐2, and SUMO‐3 in mammalian systems are found covalently attached to more than 50 proteins including p53, androgen receptor, IkBα, c‐jun, histone deacetylases (HDACs), and other proteins with major functions of SUMOylation, cytoplasmic nuclear transport, transcripton, and DNA repair …”
Section: Introductionmentioning
confidence: 99%
“…Other aspects of sumoylation, such as protein conformational changes, are not mimicked by our SIM recruitment approach and may be important for recruiting DNA repair factors. In addition to telomere binding proteins, many DNA repair factors are also sumoylated including 53BP1 and PCNA (Garvin and Morris, 2017). Sumoylation of those DNA repair factors, not captured in our dimerization approach, may be required for recruitment to APBs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many proteins involved in gene expression (transcription factors, transcription machinery, co-regulators, histones) are regulated by their SUMOylation (Neyret-Kahn et al, 2013;Cossec et al, 2018;Rosonina et al, 2017;Tempé et al, 2014;Chymkowitch et al, 2015). SUMOylation also plays key roles in DNA damage repair through the modification of many proteins involved in this process (Garvin & Morris, 2017).…”
Section: Introductionmentioning
confidence: 99%